L’exil de la loterie : du tragique de l’histoire au tragique du dérisoire dans Ce jour viendra d’Anouar Benmalek - Abdelouahab Boussaid (Multilinguales)
The exile, in Ce jour viendra by Anouar Benmalek, takes on a two-sided nature. On the one hand, it is a drift resulting from a tragedy of history aroused by a determining socio-historical context playing the role of a transcendence replacing divine fatality. On the other hand, it is a catalyst for the tragic of the derisory. The spatial mutation from Algiers to Los Angeles puts the hero in disproportionate conflict with a group of geneticists carrying out the most modern biotechnological experiments on his son by taking charge of him by using the power conferred on them by the alliance of science and finances. The dialectization of being and matter makes the dad undergo an "existential wear and tear" besieging him in endless questions about his condition that the metaphorical network of the text reduces to the rank of an animal. The exile of the lottery, initially conceived as an antidestiny, ends in destiny.